The Development Model of the Digital-Based Madrasah ‎Diniyah at Islamic Boarding School Padepokan Kyai ‎Mudrikah Kembang Kuning - Listiana, Heni; Achmad Muhlis; Vargheese K J (TADRIS: Jurnal Pendidikan Islam, 2023)
Digital era has forced all educational institutions to change, including Madrasah Diniyah. Madrasah Diniyah, as a non-formal educational institution focused on teaching Islamic values, is required to adapt to these changes to remain relevant. This research aims to explore the digital-based development model of Madrasah Diniyah at Islamic Boarding School Padepokan Kyai Mudrikah Kembang Kuning Pamekasan (IBS PKMKK). The research method applied is a case study analysis, involving data collection through interviews, observations, and the evaluation of relevant documents. This study emphasizes the suitability of this digital development model with local needs and context. Although located in rural areas, IBS PKMKK Madrasah Diniyah has adapted to the demands of the modern era without abandoning its primary focus on religious education, becoming a kind of oasis that encourages the adoption of digital-based learning in a community that previously prioritized quality education less.